Parenting Styles and Self-Efficacy of Adolescents: Malaysian Scenario (Global Journal of Human-Social Science, 2012)
Parenting styles and its impact on adolescents psychosocial development has been an area of interest in the field of psychology Previous studies have revealed that parenting styles are correlated with adolescents self-esteem drug and alcohol use delinquency and academic performance This study aimed to investigate the effect of parenting styles namely authoritative authoritarian and permissive on adolescents self-efficacy level A hundred and twenty students served as participants for this study The mean age for the entire sample was 18 441 and had an equal number of males and females A single survey was administered and data on perceived parenting styles and ratings on self-efficacy were collected Correlation was carried out and results indicated that authoritative parenting style is highly associated with self-efficacy Regression result showed that authoritative parenting style contributes 12 8 towards student s self-efficacy However authoritarian and permissive parenting styles do not produce any significant relationship when associated with self-efficacy T-test comparison revealed a significant difference of self-efficacy among the males and females The male students demonstrated higher level of self-efficacy as compared to the females This study is significant because it allows helping professionals to gain a better understanding on the relationship between parenting styles and self-efficacy
Keywords: parenting style; self-efficacy